Rigid Pavement Condition Assessment With Bina Marga Method and Pavement Condition Index (PCI) Method in Dumai - Duri City at STA 173+000 - 177+000 - Ramdhani, Fitra; Mubarak, Husni; Equinaldo, Equinaldo (-)
Appraisal the condition of the road on pavement surface is one step in the determination of maintenance management program to a road segments that need to be handled. This study pupose is to determine the road condition on the road section Dumai City - Duri precisely at STA 173 + 000-177 + 000 and also to determine the type of precise handling program in maintenance. Based on the results of the analysis, the greatest damage type, either use Bina Marga Method and PCI Method is type of slippery aggregate damage. But for the smallest percentage of damage, there is a difference between Bina Marga Method and PCI Method. This is due to a difference in the election unit examined samples. In the Bina Marga Method the smallest damage percentage is type of popouts damage while in PCI method obtained the smallest percentage value of the damage isa type of fracture damage on plate. Results of assesment rigid pavement road surface conditions at STA 173 + 000-177 + 000 in Dumai City Limits road - Duri by Bina Marga Methodobtained damage limitation percentage on 2.40% to the size of the surface layer of pavement surveyed road conditions were rated as " good (B) "the obtained result of determination program, namely road handling routine maintenance. While the results of the condition assessment of PCI method, PCI value obtained with a value on 65.25 road conditions as "Good " and the determination program of road maintenance is regular maintenance. It can be concluded that the results of assessment of the condition of Dumai City Limits road - Duri City at STA 173 + 000-177 + 000 using either a Bina Marga Methods and Pavement Condition Index (PCI) Methods in determining the assessment of road conditions and determining the program road plan maintenance obtained the same results.